The Potential of Spring Water Analysis for Drinking Water at Ujung Gagak Village, Kampung Laut Subdistrict, Cilacap Regency - Adinda Dwi Safitri; Rachmadhi Purwana; Suyud Warno Utumo (Jurnal Penelitian Pendidikan IPA, 2024)
Limited clean water is the main problem in Ujung Gagak Village. The community can use no groundwater because the water is brackish and salty, which is unsuitable for daily activities. This study aims to analyze the potential of the Karang Cave spring to be used as drinking water. This spring plays an important role in the life of the people of Ujung Gagak Village when the dry season arrives. Using the grab sampling method, raw water sampling at the Karang Cave spring. Pollution Status Index (IP) quality of 5.08 is included in the moderately polluted category. Then, raw water samples are taken and processed in the Reverse Osmosis (RO) system. Parameters that exceeded the quality standard were total coliform of > 24,000 CFU/100ml, salinity parameter of 0.33‰, turbidity of 1.98 NTU, and hardness of 320 mg/L. However, treating it in an RO system for drinking water is necessary. Laboratory test results for water quality after processing, several parameters experienced a significant decrease, for the parameter salinity to 0‰, turbidity to 0.74 NTU, and hardness to 99 mg/L, total coliform decreased by 108 CFU /100ml. The results showed that the RO system succeeded in removing salt up to 99.5% and reducing the Concentration of turbidity, hardness, and total coliform. It is suitable for drinking water, but if you want to drink it immediately, you can cook it first, considering that the total coliform is still above the required quality standard.